Gene mutation in diabetic patients with lung adenocarcinoma: a real-world retrospective cohort study - Lei Yang; Yang Hong; TingTing Zeng; HongMei Yue; DePeng Jiang (Frontiers in Medicine)
PurposeThe incidence of lung cancer is closely associated with diabetes; however, it remains unclear whether diabetes influences the genetic mutations present in lung cancer. Therefore, we will compare the genetic mutations in patients with lung adenocarcinoma (ADC) who have diabetes against those who do not.MethodsWe included 279 patients diagnosed with lung adenocarcinoma (143 with diabetes and 136 without diabetes) at the Second Affiliated Hospital of Chongqing Medical University between 2016 and 2023, and analyzed the clinical characteristics and genetic mutation profiles of all participants.ResultsIn comparison to ADC patients without diabetes, those with diabetes exhibited a lower overall gene mutation rate (49.7% vs. 65.4%, P = 0.008). Female ADC patients demonstrated a higher total gene mutation rate and EGFR gene mutation rate than their male counterparts (49.3% vs. 66.9%, P = 0.003; 27.6% vs. 58.3%, P < 0.001, respectively), although their TP53 gene mutation rate was lower (8.6% vs. 2.4%, P = 0.027). ADC patients without a smoking history had a higher gene mutation rate and EGFR gene mutation rate than those with a smoking history (62.6% vs. 47.4%, P = 0.014; 51.6% vs. 22.7%, P < 0.001, respectively), but a lower KRAS gene mutation rate (4.4% vs. 14.4%, P = 0.003). Conversely, ADC patients with a drinking history had a lower EGFR gene mutation rate than those without (48% vs. 62.6%, P = 0.018; 31.0% vs. 47.5%, P = 0.007), yet a higher KRAS gene mutation rate (14.0% vs. 4.5%, P = 0.005). Univariate and multivariate linear regression analyses revealed that being female, having no smoking history, and being in phase II or IV of tumor stage were associated with gene mutation. Subgroup analysis indicated that the rate of gene mutation in male smoking lung adenocarcinoma patients with diabetes was significantly lower than in those without diabetes.ConclusionThis retrospective study of real-world data suggests that patients with lung adenocarcinoma and diabetes may have a reduced likelihood of developing genetic mutations, particularly among male smokers. Furthermore, gender, smoking history, and tumor stage may be correlated with the presence of gene mutations.